Pemahaman Mahasiswa Muamalah IAIN Parepare terhadap Asuransi Syariah - Nur, Rahmah; Aris, Masniati; Suhermin, Mirandha; Amelia, Fausia; Nurfadilah, Nurfadilah; Hafizah, Norhana; Armila, Armila; Asikin, Risma (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2022)
Sharia insurance plays a pivotal role in offering support and protection to its members in the face of uncertainties and losses. However, the comprehension of students concerning sharia insurance exhibits a notable spectrum of variability. As such, this study endeavors to delve into the nuanced understanding of Muamalah students at IAIN Parepare regarding sharia insurance. The primary goal is to gauge the depth of knowledge these students possess in this domain. By adopting a qualitative approach, this research capitalizes on field research as its chosen methodology. The study sample encompasses 8 Muamalah students, who were thoughtfully selected to partake as respondents, contributing their perspectives through interview sessions. Through this method, a comprehensive analysis of the students' comprehension of sharia insurance was conducted. The findings yielded from the research elucidate intriguing insights into the perspectives of Muamalah students at IAIN Parepare. Among the respondents, a notable 57.2% affirmed their grasp of insurance concepts, underscoring their familiarity with the fundamental tenets of sharia insurance. Conversely, an intriguing 43.0% of participants conveyed their lack of understanding in this realm, hinting at the presence of potential gaps in the pedagogical approaches or materials employed in disseminating knowledge about sharia insurance.